Improving Team Activities in the Concept Development Stages: Addressing Radical Development and Open-Ended Problems. (3rd July 2016) - Wenngren, Johan; Ericson, Åsa; Parida, Vinit
ABSTRACT: Firms seeking radical innovation require development teams to articulate design solutions based on open-ended problems. Such problems have no single answer to the problematical situation, but have several plausible solutions. Although prior studies have highlighted the importance of prototyping or other methodologies, they provide limited guidance toward addressing open-ended problems. We investigate how teams make sense of complex design and development problems in order to benefit innovative endeavors. The results illustrate a team-level concept development model that identifies critical stages, associated activities, and influencing mind-set to explain how engineering teams overcome challenges associated with open-ended problems.